A comparison of skeletal, dentoalveolar and soft tissue characteristics in white and black Brazilian subjects - Lívia Maria Andrade de Freitas; Karina Maria Salvatore de Freitas; Arnaldo Pinzan; Guilherme Janson; Marcos Roberto de Freitas (Journal of Applied Oral Science, 2010)
OBJECTIVE: This study aimed to compare skeletal, dentoalveolar and soft tissue characteristics in white and black Brazilian subjects presenting normal occlusions. MATERIAL AND METHODS: The sample comprised the lateral cephalograms of 106 untreated Brazilian subjects with normal occlusion, divided into two groups: Group 1- 50 white subjects (25 of each gender), at a mean age of 13.17 years (standard deviation 1.07); and Group 2- 56 black subjects (28 of each gender), at a mean age of 13.24 years (standard deviation 0.56). Variables studied were obtained from several cephalometric analyses. Independent t tests were used for intergroup comparison and to determine sexual dimorphism. RESULTS: black subjects presented a more protruded maxilla and mandible, a smaller chin prominence and a greater maxillomandibular discrepancy than white subjects. Blacks presented a more horizontal craniofacial growth pattern than whites. Maxillary and mandibular incisors presented more protruded and proclined in black subjects. The nasolabial angle was larger in whites. Upper and lower lips were more protruded in blacks than in whites. CONCLUSIONS: The present study found a bimaxillary skeletal, dentoalveolar and soft tissue protrusion in black Brazilian subjects compared to white Brazilian subjects, both groups with normal occlusion. Upper and lower lips showed to be more protruded in blacks, but lip thickness was similar in both groups.